Cold resistance and metabolic responses to salinity variations in the amphipod Eusirus antarcticus and the krill Euphausia superba - Aarset, Arne V.; Torres, Joseph J. (Polar Biology, 1989)
The krill Euphausia superba, unlike the amphipod, Eusirus antarcticus, tolerates being frozen into solid sea-ice at temperatures down to about-4°C. Cooled in air, the amphipod and the krill freeze and will die at temperatures of-11° and-9°C respectively, representing the supercooling points of the animals. The krill is an osmoconformer in the salinity range of 25 to 45 ppt, while the amphipod conforms in the salinity range of 26 to 40 ppt. The animals thereby lower the melting point of their body fluids in the vicinity of the freezing sea ice, preventing internal ice formation at low temperatures. The mean oxygen consumption rates, at raised and lowered salinities, were not significantly different from rates obtained in normal (35 ppt.) seawater, indicating that salinity has little effect on the metabolism of either species.
Keywords: Sørishavet; krepsdyr; krill; kuldetoleranse; marin biologi; plankton

Size Frequency Pattern of Euphausia Superba in the Antarctic Peninsula Waters in the Austral Summer of 1983 - Fevolden, Svein Erik; George, Robert Y. (Journal of Crustacean Biology, 1984)
In the austral summer of 1983, schools of krill from Bransfield Strait and Palmer Archipelago were analyzed for composition in terms of size frequencies and maturity stages. Juveniles dominated in all schools, and mature animals never exceeded 6.8% of the animals at any sampling site. Gravid females were encountered in only four out of 15 schools and were never more frequent than 1.8% of the animals in any school. Among subadults and juveniles the largest animals were found on the inside of Palmer Archipelago. Smaller nonreproductive animals were on the outside and in Bransfield Strait. A second group of juveniles, in a size range of 12-15 mm, was more pronounced north of Crocker Passage than south of the Passage. Their potential origin from a more slowly growing and later spawning Southern Weddell Sea population is discussed. Lack of reproductive animals in the Bransfield/South Shetlands vicinity may reflect yearly variation in this region. A hypothesis is put forward on the basis of this study that Palmer Archipelago is a nursery ground for krill spawned elsewhere. The sites of origin of this krill could be ascertained on the basis of studies of enzyme polymorphism in these populations.
Keywords: Sørishavet; Weddellhavet; krepsdyr; krill; marin biologi; plankton